International Normalized Ratio Monitoring of Vitamin K Antagonist Therapy: Comparative Performance of Point-of-Care and Laboratory-Derived Testing - Bonar, Roslyn; Mohammed, Soma; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2015)
The monitoring of warfarin therapy using the international normalized ratio (INR) has now moved outside the laboratory's control by use of point-of-care (POC) devices. Although this provides patients with the convenience of immediate results and clinical assessment, POC–INRs are often performed by nonlaboratory staff with little experience in quality control. The Royal College of Pathologists of Australasia Quality Assurance Program (RCPAQAP) Haematology has devised a POC–INR external quality assessment (EQA) program that is suitable for both laboratory and nonlaboratory operators (e.g., nurses) to perform INR testing with good accuracy and precision. A comparison of the performance of the POC versus the laboratory-derived INR testing over the past 8 years has shown that the variation in test results (expressed as coefficient of variation; CV) for laboratory INRs increases with more prolonged INR values, whereas CVs for the POC–INR testing were generally lower, with a reduced dependency on INR values. In our program, the CoaguChek XS (Roche, Basel, Switzerland) showed the best performance among the POC devices. A comparative assessment with other EQA providers showed agreement and disparity with our data in terms of comparative CVs obtained between the laboratory and POC–INRs. The growth of the RCPAQAP POC–INR program from 29 to 360 in the past 12 years highlights the importance of providing suitable EQA for POC–INR staff who are unfamiliar with laboratory practice. This helps maintaining consistent results, which have important implications for the therapeutic management of patients on vitamin K antagonist therapy.
Keywords: international normalized ratio; point of care; external quality assessment; proficiency testing